City profile: Ningbo - Tang, Yu-Ting; Chan, Faith Ka Shun; Griffiths, Jim (Elsevier, 2015)
Ningbo is located in the south-east of Yangtze River Delta by the East China Sea, 220 km south of Shanghai. The city has been an important port in East China for foreign trade since 7th century. Since 1980s, encouraged by China’s economic “open-door” policy, one of the ways the city attracted foreign investment and thus grew its economy was by establishing multi-functional economic development zones near its deep-water port. As a result, Ningbo is now one of the top ten coastal ports in the world (as measured in Twenty-Foot Equivalent Units, TEUs). Similarly, the city’s GDP per capita is approximately three times the national average. The current and historic prosperity of Ningbo is in no small way related to its geographical position, just 20 km inland from the Hangzhou estuary and the gateway to the East China Sea. It is also the approximate centre of a 1000 km2 coastal plain, at the confluence of the Fenghua and Yao Rivers, and from where the Yong River leads to the sea. However, also a result of this geographic location the city is now facing an increasing risk of coastal flooding caused by increase in urban area; climate change (increased rainfall intensity); and predicted sea-level rise. As a result both water management and current flood management practice (and related infrastructure) are under scrutiny. In addition to describing the evolution of the city, this paper focuses on the implication of current planning practices in Ningbo, which aim to ensure the sustainable development of the city both in terms of its natural resources and its expected rate of economic growth.